Sea turtles across the North Pacific are exposed to perfluoroalkyl substances. (15th June 2021) - Wood, Cathryn; Balazs, George H.; Rice, Marc; Work, Thierry M.; Jones, T. Todd; Sterling, Eleanor; Summers, Tammy M.; Brooker, John; Kurpita, Lauren; King, Cheryl S.; Lynch, Jennifer M.
Abstract: Perfluorinated alkyl substances (PFASs) are global, persistent, and toxic contaminants. We assessed PFAS concentrations in green ( Chelonia mydas ) and hawksbill ( Eretmochelys imbricata ) turtles from the North Pacific. Fifteen compounds were quantified via liquid chromatography tandem mass spectrometry from 62 green turtle and 6 hawksbill plasma samples from Hawai'i, Palmyra Atoll, and the Northern Marianas Islands. Plasma from 14 green turtles severely afflicted with fibropapillomatosis, and eggs from 12 Hawaiian hawksbill nests from 7 females were analyzed. Perfluorooctane sulfonate (PFOS) predominated in green turtle plasma; perfluorononanoic acid (PFNA) predominated in hawksbill tissues. Concentrations were greater in hawksbill than green turtle plasma (p < 0.05), related to trophic differences. Green turtle plasma PFOS concentrations were related to human populations from highest to lowest: Hawai'i, Marianas, Palmyra. Influence on fibropapillomatosis was not evident. PFASs were maternally transferred to hawksbill eggs, with decreasing concentrations with distance from airports and with clutch order from one female. A risk assessment of PFOS showed concern for immunosuppression in Kailua green turtles and alarming concern for hawksbill developmental toxicity. Perfluoroundecanoic (PFUnA) and perfluorotridecanoic (PFTriA) acid levels were correlated with reduced emergence success (p < 0.05). Studies to further examine PFAS effects on sea turtle development would be beneficial. Graphical abstract: Image 1 Highlights: Perfluorinated alkyl substances were detected in sea turtles from the North Pacific. PFAS levels in sea turtles were correlated with human population and land use. Maternal offloading of PFASs was detected in unhatched hawksbill eggs from Hawaii. Levels in eggs were near those which have caused developmental toxicity in birds. No correlation was found between fibropapillomatosis (FP) and PFAS concentrations. Abstract : Endangered or threatened sea turtle species at remote Pacific islands contain perfluoroalkyl substances in blood and offload them to eggs, at concentrations known to be detrimental in birds.